2006
DOI: 10.1073/pnas.0510708103
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-1 uses phospholipase D1 as a negative regulator of β-amyloid formation

Abstract: Presenilin (PS1͞PS2) is a major component of ␥-secretase, the activity that mediates proteolysis of ␤-amyloid precursor protein to generate ␤-amyloid (A␤). Here we demonstrate that PS1, through its loop region, binds to phospholipase D1 (PLD1), thereby recruiting it to the Golgi͞trans-Golgi network. Overexpression of wildtype PLD1 reduces A␤ generation. Conversely, down-regulation of endogenous PLD1 by small hairpin RNA elevates A␤ production. The A␤-lowering effect of PLD1 is independent of its ability to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 36 publications
4
76
1
3
Order By: Relevance
“…Thus, our study raises the possibility that PIP 2 may play a key role in the multiple cellular defects associated with presenilin FAD mutations. Cai et al (46) recently reported that PS1 FAD is associated with aberrant phospholipase D (PLD) activity, and PLD supplementation reverses FAD phenotypes. Interestingly, PLD enzymatic activity is critically dependent on PIP 2 , and the major product of PLD activity (PA) stimulates the production of PIP 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study raises the possibility that PIP 2 may play a key role in the multiple cellular defects associated with presenilin FAD mutations. Cai et al (46) recently reported that PS1 FAD is associated with aberrant phospholipase D (PLD) activity, and PLD supplementation reverses FAD phenotypes. Interestingly, PLD enzymatic activity is critically dependent on PIP 2 , and the major product of PLD activity (PA) stimulates the production of PIP 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In a companion report (15), it is demonstrated that PLD1, through a mechanism independent of ␤APP trafficking, compromises the integrity of the ␥-secretase complex and thereby inhibits ␤-amyloid formation. These combined actions of PLD1 suggest the development of therapeutic approaches for restoring neuronal dysfunctions in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in view of the multiple substrates of these secretases, designing drugs for specific inhibition of APP β-and γ-cleavage appears challenging. Previous reports have shown that altered cell signaling, especially G protein-coupled receptor (GPCR) signaling, is related to abnormal Aβ production and AD pathogenesis [19][20][21][22][23]. We have previously reported that activation of β2-adrenergic receptor (β 2 -AR) or δ-opioid receptor (DOR) directly enhances γ-secretase activity and accelerates Aβ production [23].…”
Section: Introductionmentioning
confidence: 99%